2015
DOI: 10.1021/acs.jmedchem.5b00455
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia-Sensitive Metal β-Ketoiminato Complexes Showing Induced Single-Strand DNA Breaks and Cancer Cell Death by Apoptosis

Abstract: A series of ruthenium and iridium complexes have been synthesised and characterised with 20 novel crystal structures discussed. The library of -ketoiminato complexes has been shown to be active against MCF-7 (human breast carcinoma), HT-29 (human colon carcinoma), A2780 (human ovarian carcinoma) and A2780cis (cisplatin resistant human ovarian carcinoma) cell lines, with selected complexes being more than three times as active as cisplatin against the A2780cis cell line. Complexes have also been shown to be hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
47
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 59 publications
(50 citation statements)
references
References 41 publications
2
47
1
Order By: Relevance
“…Ru(II) complexes with N,O -ligands were synthesized by Lord et al . 159 Most of the complexes were cytotoxic effect in HT-29 and MCF-7 cell lines, with significantly greater efficacy in A2780 and A2780cisR cells. In addition, the complexes were also cytotoxic to the hypoxic HT-29 cells.…”
Section: Arene Ruthenium(ii) Complexesmentioning
confidence: 92%
“…Ru(II) complexes with N,O -ligands were synthesized by Lord et al . 159 Most of the complexes were cytotoxic effect in HT-29 and MCF-7 cell lines, with significantly greater efficacy in A2780 and A2780cisR cells. In addition, the complexes were also cytotoxic to the hypoxic HT-29 cells.…”
Section: Arene Ruthenium(ii) Complexesmentioning
confidence: 92%
“…24 We have previously reported a range of iridium picolinamide complexes that inhibit Trx-R, with IC 50 values in the nanomolar range. 19,25 This prompted us to investigate whether these novel complexes 2b, 2c, 2d, 3a and 3b reported here are also able to inhibit Trx-R activity. Significantly, all the active rhodium and iridium functionalised Cp ‡ dimers were found to be potent Trx-R inhibitors with IC 50 values in the nanomolar or low micromolar range (Table 3 and Figure S1).…”
Section: Please Do Not Adjust Marginsmentioning
confidence: 95%
“…16 Therefore, breaking up the rhodium and iridium dihalide Cp* dimers with different bidentate ligands led to the development of complexes which show high in vitro cytotoxic activity against tumour cell lines. [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] Where tested, studies have reported negligible activities of the starting dimers, i.e. [Cp*MCl 2 ] 2 (M = Rh or Ir) 16 (M = Rh or Ir).…”
mentioning
confidence: 99%
“…[41,42] More recently,G lazer and co-workers have compared the activities of cis-[Ru(bpy) 2 Cl 2 ]( bpy = 2,2'-bipyridine) with trans-[Ru(qpy)Cl 2 ]( qpy = 2,2':6',2'':6'',2'''-quaterpyridine), finding the trans isomer to be 7-10 times more active than the cis isomer. [43] This propensityf or the formation of different isomersi so ne of the reasonst hat there has been much effort dedicated to the synthesis and development of transition-metal-based candidates that are based on the molecular architectures associatedw ithM -arene, [44][45][46][47][48][49][50][51] MCp* [47,[52][53][54][55][56][57] and ferrocened erivatives. [58,59] The complexation of ruthenium to picolinamidel igandsi so f interestb ecause of its relevance to previously reported metalion peptide chemistry and the possibility of different ligand bindingm odes that can potentially alter the biological activity of the complexes.…”
Section: Introductionmentioning
confidence: 99%